Human learning and memory - Lieberman, David A. (Cambridge University Press, 2012)
"This innovative textbook is the first to integrate learning and memory, behaviour and cognition. It focuses on fascinating human research in both memory and learning (while also bringing in important animal studies) and brings the reader up to date with the latest developments in the subject. Students are encouraged to think critically - key theories and issues are looked at in detail, descriptions of experiments include why they were done and how looking at the method can help evaluate competing viewpoints. By looking at underlying cognitive processes, students come away with a sense of learning and memory being interrelated actions taken by the same human being, rather than two separate activities. Lively and engaging writing is supported by lots of examples of practical applications that show the relevance of lab-based research to everyday life. Examples include treatments for phobias and autism, ways to improve eyewitness testimony and methods of enhancing study techniques"--